Research on Plant Growth of Genotypes of Arabica Coffee on Water Stress - Malau, Sabam; Siagian, Albiner; Sirait, Bilter; Ambarita, Himsar; Sihotang, Maria Rumondang; Naibaho, Benika (Advanced Aspects of Engineering Research Vol. 5, 2021)
Drought tolerant genotype has to be created due to changing of world climate. Performance of Arabica coffee offspring might be affected by parental environment. In North Sumatra province of Indonesia, Arabica coffee were growing at a wide range of elevation, precipitation and temperature. Hence, drought tolerant genotype might be available in this coffee plantation. The objectives of this research were to determine effect of water stress on performance Arabica coffee genotypes. Seven genotypes which were selected from seven different environments as well as four level of water treatments (100%, 75%, 50%, and 25% field capacity) were used. Paramaters were increment of plant height, stem diameter, and leaf number. Factorial experiment namely completely block design with two factors and three replications was conducted in the green house. The result revealed that interaction of genotype and level of water treatment was highly significant. It could be concluded that it could be possible to carry out selection for drought tolerant genotype from the existing population of Arabica coffee. However, selection should be conducted in a controlled condition due to significant GxE interaction.